Epitaphia Vergilii - STOK, Fabio (AL. Rivista di studi di Anthologia Latina, 2013)
Abstract In this paper, the 24 epitaphs of Virgil included in the Symposium XII sapientum (507-518 and 555-566 Riese2) are examined. They are imitations of the best known of Virgil’s epitaph Mantua me genuit, but also reveal the influence of Virgil’s biographic tradition. Particular attention is paid to the relation between the epitaphs and the Life of Virgil by the grammarian Phocas.